2015
DOI: 10.1111/gcb.12800
|View full text |Cite
|
Sign up to set email alerts
|

Pyrogenic organic matter production from wildfires: a missing sink in the global carbon cycle

Abstract: Wildfires release substantial quantities of carbon (C) into the atmosphere but they also convert part of the burnt biomass into pyrogenic organic matter (PyOM). This is richer in C and, overall, more resistant to environmental degradation than the original biomass, and, therefore, PyOM production is an efficient mechanism for C sequestration. The magnitude of this C sink, however, remains poorly quantified, and current production estimates, which suggest that ∽1-5% of the C affected by fire is converted to PyO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
229
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 243 publications
(233 citation statements)
references
References 71 publications
2
229
2
Order By: Relevance
“…Together, the temperature ranges reported from these experimental fires suggest that the mean temperature at the floor forest during fire in conifer forests may range between 300 and 750 °C and that the temperature in the canopy may reach 650 °C. Although the study conducted by Santín, et al [12] also focused on jack pine forest, their study was conducted in the boreal region and their study site supported a deep moss layer and saturated mineral soil. Jack pine forests in our study site are more ecologically similar to the pitch pine forests in the New Jersey, USA pine barrens because both forest types have thin forest floors and are found on dry sandy soils [37].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Together, the temperature ranges reported from these experimental fires suggest that the mean temperature at the floor forest during fire in conifer forests may range between 300 and 750 °C and that the temperature in the canopy may reach 650 °C. Although the study conducted by Santín, et al [12] also focused on jack pine forest, their study was conducted in the boreal region and their study site supported a deep moss layer and saturated mineral soil. Jack pine forests in our study site are more ecologically similar to the pitch pine forests in the New Jersey, USA pine barrens because both forest types have thin forest floors and are found on dry sandy soils [37].…”
Section: Discussionmentioning
confidence: 99%
“…Wildfires can have a greater range in temperature than prescribed fires. For example, Hartford and Frandsen [35] found that the litter surface, duff, and soil surface reached 300, 515, and 400 °C, respectively, in a prescribed ground fire in mixed-conifer forests (Larix occidentalis and P. contorta) in western Montana, whereas Santín, et al [12] found that the mean temperature during an experimental stand-replacing crown fire in a jack pine forest in Canada was <70 °C at the mineral soil surface and 750 °C at the surface of the forest floor. Furthermore, Schneider, et al [36] in a study of experimental fire in pitch pine (P. rigida Mill) forest in New Jersey, found that temperatures in the canopy can reach 510-650 °C during a crown fire whereas temperatures in the canopy during surface fire range between 0 and 260 °C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations